THE REALITY AND GROWTH MANAGEMENT OF UKRAINIAN BUSINESS DURING WARTIME - Ставнича, Наталія Ігорівна; Кінаш , Ірина Петрівна; Kashka, Dmytro (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
The article is aimed at researching the realities and drowth directions of Ukrainian entrepreneurship functioning under modern conditions. It has been found that conducting business during the war arises many challenges for entrepreneurs. Despite unprecedented losses and challenges due to the war, Ukraine managed to maintain relative macroeconomic and price stability and overcome significant difficulties. Ukrainian business persisted and began to develop actively in 2023. Three quarters of large and medium-sized enterprises in Ukraine recorded profit before taxation for 3 quarters of 2023. This demonstrated the ability to adapt to wartime conditions. The best financial results are demonstrated by financial and insurance companies, industry, wholesale and retail trade, and car repair. The fastest rates of recovery are observed in such sectors as: construction, domestic trade, agriculture, processing industry. The index of business activity in Ukraine has been growing and now stands at 37.3. Three out of four companies in Ukraine rate their financial and economic condition as satisfactory. It has been established that the biggest obstacles to business recovery are the following reasons: unpredictabilityof the development situation, the domestic market, the unpredictable actions of the state, and the lack of a sufficient number of solvent customers. Entrepreneurs consider the eradication of corruption and the need to improve access to credit resources as a high priority task for the government. Labor is considered as the most important resource for the business growth in Ukraine. The following areas of business growth were formed: improving access to financing for micro, small and medium-sized enterprises; increasing human capital and increasing the flexibility of the labor market; salary increase; increasing competitiveness; promoting the business development of veterans.